Inhibition of selective factor Xa suppresses type 1 diabetes development in mice via the CXCL16 chemokine - Mohamed S. Abdel-Bakky; Hamdoon A. Mohammed; Elham Amin (Pharmacia)
Type 1 diabetes mellitus (T1DM) is associated with enhanced thrombosis potential. This research aims to investigate the role of coagulation system activation and CXCL16 in T1DM progression and the possible preventive effect of the selective Factor Xa inhibitor, Fondaparinux (Fond). Forty male Wistar albino mice were classified into 4 groups. Control, Fond, Streptozotocin (STZ), and Fond + STZ groups. Biochemical, hematological, and histopathological parameters, expressions of CXCL16, insulin, fibrinogen, and PAR-2, were investigated. A significant increase in blood glucose level and expressions of CXCL16, fibrinogen, and PAR-2, together with histological and nuclear changes in the pancreatic islets, was observed in STZ-treated mice, accompanied by a reduction in the serum insulin level. Fond improved the deleterious effects resulting from STZ treatment. In conclusion, coagulation system activation and CXCL16 play a critical role in the initiation of T1DM and could be used as therapeutic targets for T1DM prevention.